2020
DOI: 10.1177/0898264320966266
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in the Use of Health Information Technology Among Adults in the United States: An Analysis of the Health Information National Trends Survey

Abstract: Background: Despite significant advancements in the use of health information technologies (HITs) in health care, older adults’ adoption of new technologies has consistently lagged behind that of younger adults. Objective: To compare ownership rates and preferences for utilizing technology for health information exchange among older and younger adults. Methods: Utilizing data from the 2017 and 2018 iterations of the Health Information National Trends Survey ( n = 6789), we performed multivariable logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 37 publications
2
13
1
Order By: Relevance
“…This spanned from daily use to no use at all. The majority of the informants used ICT on a daily basis, which was in alignment with former studies [ 15 , 21 , 32 ] as well as with data from Statistics Denmark, showing that 51% of the 65-74 year olds and 26% of the 75-89 year olds use the internet on a daily basis [ 20 ]. Several informants had experiences with health-related ICT use.…”
Section: Discussionsupporting
confidence: 86%
“…This spanned from daily use to no use at all. The majority of the informants used ICT on a daily basis, which was in alignment with former studies [ 15 , 21 , 32 ] as well as with data from Statistics Denmark, showing that 51% of the 65-74 year olds and 26% of the 75-89 year olds use the internet on a daily basis [ 20 ]. Several informants had experiences with health-related ICT use.…”
Section: Discussionsupporting
confidence: 86%
“…Our study participants may not be representative of older adults generally as the study only includes people who opted into a digital MSK program. First, a previous study of a nationally representative sample of older adults found that older adults are less likely to use health information technology vs. younger adults (35). In contrast, our study suggests that older adults who do choose to use a digital MSK program are even more engaged than younger adults.…”
Section: Discussioncontrasting
confidence: 58%
“…Among cancer survivors, not having a college degree, older age and low‐income were associated with less chance of using DHT. Despite the lag in using new technologies among older adults, the technology landscape is a rapidly changing field—this trend is likely to shift over time, as this demographic group increasingly adopts digital devices for managing their health conditions 36,37 . Additionally, socioeconomic status (SES), a metric for patients' capacity to access appropriate medical care, is associated with cancer outcomes—lower SES is associated with poor outcomes across several cancer diagnoses 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lag in using new technologies among older adults, the technology landscape is a rapidly changing field-this trend is likely to shift over time, as this demographic group increasingly adopts digital devices for managing their health conditions. 36,37 Additionally, socioeconomic status (SES), a metric for patients' capacity to access appropriate medical care, is associated with cancer outcomes-lower SES is associated with poor outcomes across several cancer diagnoses. 38,39 More recently, a cross-sectional nationwide study revealed that although DHT usage has increased over the last decade in the United States, substantial socioeconomic disparities still exist in DHT usage, which could potentially exacerbate health disparities.…”
mentioning
confidence: 99%